CHARACTER EDUCATION VALUES IN HAJAT SASIH CEREMONY - Haerudin, Dingding; Manullang, Tryastuti Irawati Belliny; Maulana, Farid Rizqi (UPI, 2021)
Abstract:Â The purpose of this research is to describe the values of character education found in Hajat Sasih ceremony in Â Kampung Naga, Jawa Barat, Indonesia. The method used in this study is a qualitative method with a descriptive analytical approach. The data collected through observation, interviews, and literature study on the procession from its preparation (tatahar), implementation to closure. The results of the study show that the advancement of the world and the growth of increasingly modern technology have not had much influence on the lives of people in Kampung Naga. At Hajat Sasih ceremony the attributes of character education are found including being religious as shown on the purpose of the ceremony itself as an expression of gratitude to the God and ask for the protection, being discipline which shown on their obedience in performing the ceremony six times a year and follow the rules in its implementation, having patriotism, having reverence, building and maintaining friendship, sustaining the environment, developing social care, and showing responsibility. These characters can also be found among the people of Kampung Naga in their daily lives. As part of an attempt to retain culture and grow characters, parents reiterate the narratives to the younger communities.Â